Kv3.3b expression defines the shape of the complex spike in the Purkinje cell - Veys, Ken; Snyders, Dirk; De Schutter, Erik (Frontiers in Cellular Neuroscience, 2013)
The complex spike (CS) in cerebellar Purkinje Cells (PC) is not an all-or-nothing phenomena as originally proposed, but shows variability depending on the spiking behavior of the Inferior Olive and intrinsic variability in the number and shape of spikelets. The spikelets are repolarised by a sole channel, Kv3.3b, which has been proposed to undergo developmental changes during the postnatal PC maturation. We address here the regulation of the intrinsic CS variability by the expression of inactivating Kv3.3 channels in PCs by combining patch-clamp recordings and single-cell PCR methods on the same neurons, using a technique that we recently optimized to correlate single cell transcription levels with membrane ion channel electrophysiology. We show that while the inactivating TEA sensitive Kv3.3 current peak intensity increases with postnatal age, the channel density does not, arguing against postnatal developmental changes of Kv3.3b expression. Real time PCR of Kv3.3b showed a high variability from cell to cell, correlated with the Kv3.3 current density and suggesting that there are no mechanisms regulating these currents beyond the mRNA pool. We show a significant correlation between normalized quantity of Kv3.3b mRNA and both the number of CS spikelets and their rate of voltage fluctuation, linking the intrinsic CS shape directly to the Kv3.3b mRNA pool. Comparing the observed cell-to-cell variance with studies on transcriptional noise suggests that fluctuations of the Kv3.3b mRNA pool are possibly not regulated but represent merely transcriptional noise, resulting in intrinsic variability of the CS.